2016
DOI: 10.1377/hlthaff.2015.1661
|View full text |Cite
|
Sign up to set email alerts
|

Medical Marijuana Laws Reduce Prescription Medication Use In Medicare Part D

Abstract: Legalization of medical marijuana has been one of the most controversial areas of state policy change over the past twenty years. However, little is known about whether medical marijuana is being used clinically to any significant degree. Using data on all prescriptions filled by Medicare Part D enrollees from 2010 to 2013, we found that the use of prescription drugs for which marijuana could serve as a clinical alternative fell significantly, once a medical marijuana law was implemented. National overall redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
233
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 289 publications
(263 citation statements)
references
References 11 publications
23
233
6
Order By: Relevance
“…This is an important area for future research as the interaction effects between cannabis and opioids have not been fully investigated. 30,31 Interestingly, some studies have found that jurisdictions where cannabis is available for therapeutic purposes tend to see a decrease in prescription opioid/pain medication use, 32,33 suggesting that some people with chronic pain may be using therapeutic cannabis as a substitute for prescription opioids. 34,35 This study also indicated that among those who reported CUTP, 15.2% reported that they had medical approval to use cannabis therapeutically.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important area for future research as the interaction effects between cannabis and opioids have not been fully investigated. 30,31 Interestingly, some studies have found that jurisdictions where cannabis is available for therapeutic purposes tend to see a decrease in prescription opioid/pain medication use, 32,33 suggesting that some people with chronic pain may be using therapeutic cannabis as a substitute for prescription opioids. 34,35 This study also indicated that among those who reported CUTP, 15.2% reported that they had medical approval to use cannabis therapeutically.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when states regulate access to controlled substances, they are able to consider sample legislation available through the National Alliance for Model State Drug Laws. Standardized versions of state laws for policies like the medicinal use of marijuana allow researchers to conduct studies using categorizations of states, exploiting variations in the year of adoption to implement a study with a DID design (22,81).…”
Section: Policy Variation and Heterogeneitymentioning
confidence: 99%
“…Third, our findings contribute to the economic literature on policy spillover effects. Previous studies show that MMLs have spillover effects to public insurance programs (Bradford & Bradford, 2016. Moreover, there is a broader economic literature on policy spillovers.…”
mentioning
confidence: 99%